Komunitas serangga pada tanaman orok-Orok (Crotalaria striata) di berbagai habitat - Hasmiandy Hamid; Damayanti Buchori; Syafrida Manuwoto; Hermanu Triwidodo (Perhimpunan Entomologi Indonesia, 2007)
To study insect community at orok-orok plantation (Crotalaria striata) from different habitat, we observed insects that interacted with Crotalaria plantation. There were four habitat type that used in this research, habitat open area and others were agroforestry habitat. We counted about nine ordo from insect that interacted with Crotalaria plant. More than 70% member of ordo, include to Hymenoptera, specially Formicidae. Not all function member of the ordo that known, but some of them are pollinator, parasitoid, predator and herbivore.